Facts and values in students' reasoning about gene technology in the frame of risk – a thick comprehension. Issue 9 (1st August 2022) - Lundegård, Iann; Arvanitis, Leena; Hamza, Karim; Schenk, Linda; Wojcik, Andrzej; Haglund, Karin
Abstract: In the current debate, there is no consensus on the relationship between knowledge and values in students' reasoning and argumentation in socio-scientific and sustainability issues, i.e. if these should be addressed as separate entities or rather treated as a whole. In this study, we address this question empirically, with students engaging in two language games – aesthetic and epistemological – as they deliberate on ethical issues associated with genetic engineering. The study reports on a course unit that includes lectures, group work and student-led value-clarification exercises. The ways in which the language games interact were analysed using the established methods of Practical Epistemology Analysis (PEA) and analysis of Deliberative Educational Questions (DEQ). Our results show that aesthetic and epistemological language games were intricately intertwined in the students' reasoning. Given this close entanglement, each language game was conducive to the development of the other and in so doing, deepened the understanding of the content as a whole.